2021
DOI: 10.1093/ve/veab077
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic epidemiology reveals the reduction of the introduction and spread of SARS-CoV-2 after implementing control strategies in Republic of Korea, 2020

Abstract: Genomic epidemiology is a core component in investigating the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In this study, the efficacy of control strategies in South Korea was evaluated using genomic epidemiology based on viral genome sequences of 2,065 SARS-CoV-2 cases identified in South Korea from January 2020 to December 2020. Phylogenetic analysis revealed that the majority of viruses introduced from inbound travelers did not further spread throughout South Korea; however, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…COVID-19 infections surged in the Republic of Korea during the first wave in the first half of 2020, second wave in the second half of 2020, third wave between November 2020 and early 2021, and delta variant-led fourth wave which is still ongoing. Most deaths occurred in patients with comorbidities or in elderly patients with compromised immunity ( Cherian et al, 2021 ; Kwon et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 infections surged in the Republic of Korea during the first wave in the first half of 2020, second wave in the second half of 2020, third wave between November 2020 and early 2021, and delta variant-led fourth wave which is still ongoing. Most deaths occurred in patients with comorbidities or in elderly patients with compromised immunity ( Cherian et al, 2021 ; Kwon et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Human interventions such as isolation or quarantine of the population, restricting mobility between countries, and vaccination programs could impact negatively on the Ne of the variants. Other studies have reported that the COVID-19 control programs have had a negative impact on the Ne of SARS-CoV-2 ( Kwon et al, 2021 ). Interestingly, the Mexican variant presented a strong bottleneck from April 2021 onwards, which coincided with the decline of the number of cases at the end of the second wave, and the emergence and spread of the Alpha, Gamma, and Delta VOCs, which are more transmissible ( Thye et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The B.1.497 lineage was first detected in South Korea in March 2020 and was a dominant subgroup until April 2021 [ 32 ]. This lineage was dynamically associated with visitors to clubs and bars in Itaewon, Seoul, from April 29 to 6 May 2020, and caused one of the major local and long-term epidemics in South Korea [ 33 ]. A total of 3180 sequences in Korea have been uploaded in GISAID.…”
Section: Discussionmentioning
confidence: 99%